Austin Powers, the spy who shagged me [videorecording (DVD)] - Myers, Mike, 1963-; Myers, Mike, 1963-; Graham, Heather, 1970-; York, Michael, 1942-; Wagner, Robert, 1930-; Green, Seth, 1974- (New Line platinum series., 1999)
Intent on world domination, diabolical genius Dr. Evil travels back to 1969 and steals Austin's "mojo". Now Austin must return to the swingin' sixties, recover his mojo and stop his nemesis from liquidating the world.